Pelatihan Perancangan Desain Grafis dengan Menggunakan Aplikasi Canva pada SMK Swasta PAB 12 Saentis - Titin Setiawati; Muhammad Sabri; Teuku Faturrahman (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Graphic design has become a necessity in various areas of life, including branding and website design. Nowadays, graphic design has become an important part of various sectors of life, especially to support the economic and marketing sectors. Therefore, graphic design visual arts abilities and skills are very necessary. This is an opportunity to equip young people with graphic design skills. The results of a survey conducted by the service team showed that Medan city teenagers have a high interest in graphic design art. So real efforts need to be made to equip Medan city teenagers with graphic design skills. Therefore, in this community service activity, graphic design training and assistance was carried out using the Canva application to increase the creativity of Medan city teenagers. The method of implementing community service is in the form of lectures providing material directly by resource persons to partners.